Probable model of relaxation polarization in polycrystalline lithium-titanium ferrite; Modern Techniques and Technologies MTT' 2003 - Malyshev A. V. (2003, 2003)
A study was conducted to determine the temperature dependencies epsiv' (T) and epsiv" (T) obtained for Li-Ti ferrite at different test signal frequencies and amplitudes. The empirical expressions sufficiently describing the relaxation polarization in the investigated frequency and temperature ranges were obtained and the frequency-independent parameters appearing in the expressions were determined. The results show that the relaxation polarization activation energy is not equal to the transfer charge activation energy, and that the conductance does not depend on frequency. Thus, the interlayer polarization makes a little contribution to formations of large values of epsiv